1987
DOI: 10.1209/0295-5075/3/3/010
|View full text |Cite
|
Sign up to set email alerts
|

Surface Study of Langmuir-Blodgett Films by Electron Microscopy and X-Ray Reflectivity

Abstract: Using the combination of electron microscopy and X-ray reflectivity, we have * * *We wish to thank M. DUPEYRAT, C. WILLIAMS and M. KLEMAN for helpful discussions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…This cannot be explained by regular damping with increasing incidence, since there is about one order in magnitude between the intensities. The [22,23] and with our observations made by electron microscopy on replicas [24]. Micrographs taken on these samples look rather blurred, on account of the disorder of the last layer.…”
supporting
confidence: 62%
“…This cannot be explained by regular damping with increasing incidence, since there is about one order in magnitude between the intensities. The [22,23] and with our observations made by electron microscopy on replicas [24]. Micrographs taken on these samples look rather blurred, on account of the disorder of the last layer.…”
supporting
confidence: 62%
“…In x-ray diffraction from organic thin films the refractive index n can be approximated by nϭ1Ϫ␦ with ͑absorption can be neglected 8 …”
Section: A Fresnel Reflectivity From Smooth and Rough Interfacesmentioning
confidence: 99%
“…The bulk structures of Langmuir−Blodgett (LB) thin films have been extensively investigated by several methods including X-ray scattering, neutron scattering, and vibration spectroscopy due to their potential applications in the field of functional materials and biomembranes. Recently, it has been shown that the surface structures of the LB films are different from those normally expected for the bulk structure of multilayer LB films. , The scattering measurements demonstrated that the top layer of the LB film of the fatty acid is rather disordered compared with their inner layers. On the other hand, several atomic force microscopy (AFM) observations showed that wide long-range ordered domains with some irregularly distributed holes to a depth of one or two bilayers exist on the surface of the LB films. Schwartz et al investigated the morphologies of the LB films of a fatty acid on Si or mica surfaces by AFM during its submerging process in a buffered aqueous subphase and found that the reorganization of the LB films takes place from the bilayer step defects. ,, They attributed the driving force for the reorganization to be the formation of headgroup−headgroup interfaces, which are stabilized by the strong electrostatic interaction with divalent metal cations at the expense of the headgroup−substrate and headgroup−water interfaces. ,, The reorganization phenomenon has also been observed for other LB films. ,, On the other hand, it is well-known that the divalent metal cation plays an important role in forming stable multilayer LB films of fatty acid but its role in the surface structure of the LB film is still not very clear. Not only the morphology of the LB films but also the quantitative characterization of the surface molecular structures of LB films by vibration spectroscopy is strongly expected to provide a better understanding of the surface reorganization process.…”
Section: Introductionmentioning
confidence: 99%